An Attempt to Recover a Paleomonsoon Signal in the Chinese Loess Plateau Using Anisotropy of Magnetic Susceptibility - Xian, Feng; Zhang, Rui (Frontiers in Earth Science, 2020)
The paleowind direction in the Chinese Loess Plateau (CLP) was studied using anisotropy of magnetic susceptibility (AMS) data. Magnetic fabrics were examined for the last glacial loess (L1) and last inter-glacial paleosol (S1) in the southern and central CLP along a present day precipitation zone of 600 mm per year. Statistical analyses of AMS ellipsoid orientations indicate that strong rainwater events may cause random distributions in the maximum axis of the AMS azimuth, but with no deviation in the vertical plane for the average minimum axis. As high rainfall can distort paleowind determinations, it is challenging to conduct paleowind studies on the southern CLP - a topography with high precipitation density.